Experimental study of the protective effect of tuberculosis vaccines - D. T. Levy (Биопрепараты: Профилактика, диагностика, лечение, 2018)
The article presents the results of a retrospective analysis of experimental data on the protective properties of the three seed lots of tuberculosis vaccines which have been used in the production of BCG and BCG-M vaccines since 1984. It was shown that these seed lots have comparable characteristics of viability, which accounts for their equivalent immunogenicity. An additional study of the protective properties of the preparations was carried out in guinea pigs vaccinated with production batches of tuberculosis vaccines containing a different amount of viable BCG cells in the vaccine dose. Exposure of animals to a virulent strain of M. tuberculosis 2.5 months after the vaccination demonstrated high immunogenicity of the tuberculosis vaccines. It was established that a fivefold reduction in the dose of a vaccine with a high content of viable BCG cells only slightly reduces the degree of protection of the animals from disseminated tuberculosis. Thus, the data obtained confirmed that the 30 % reduction of the upper limit of the viability (viable BCG) of the BCG and BCG-M tuberculosis vaccines aimed at reducing their reactogenicity does not affect the protective properties of the preparation. It is important to note that previous post-marketing surveillance of such improved vaccines has shown a significant reduction in the number of post-vaccination complications in children.